Smoking habits of long-term survivors of surgery for lung cancer. Issue 5 (May 1982) - Davison, A G; Duffy, M
Abstract : The smoking habits of 52 patients who had survived more than five years after treatment for lung cancer were studied. Fifty-six per cent had stopped smoking before operation but this was not an early feature of the disease. No patients smoked in the immediate postoperative period but 48% became regular smokers again, usually within a year of the operation. Those who had stopped before, rather than after, their operation were more likely to remain nonsmokers. Doctors were usually unsuccessful in persuading those patients who had restarted after surgery to stop smoking. Patients undergoing surgery for lung cancer should be advised to stop smoking before the operation. Those in whom resection is successful should receive regular support and encouragement from doctors, especially in the first postoperative year, to continue as nonsmokers.